Analysis of Key Variables in Women'S Involvement in Supporting Sustainable Tourism in Penglipuran Village Bangli Regency - Hidayat, Syaharani Lutfia; Saskara, Ida Ayu Nyoman (Ekonomis: Journal of Economics and Business, 2024)
The success of Bali tourism has become a legend in itself when discussing international tourism. Tourism as a business image is essentially a meeting of local culture in the Province of Bali with the culture of tourists, seen in Penglipuran Tourism Village. The existence of cultural values can be seen from the residents' houses in Penglipuran Village which have a unique traditional building arrangement and form so that they have received many awards. In addition, most traders and workers in the future are women and become challengers, because of internal competition and the development of modern shops around Penglipuran Tourism Village, so this research needs to be conducted to find out the variables that are important to identify and support women tourism actors. in supporting the socialization of Penglipuran tourism village. This research took place in Penglipuran Village, Bangli Regency, using observation and questionnaire methods related to supporting sustainable tourism in Penglipuran Village, Bangli Regency. The approach used in this research is the Mixed Method approach. The sample in this study were 30 local community respondents and stakeholders or experts. The sample used in this study consisted of the community and traders in Penglipuran Village who could provide an assessment and suitability for the conditions that occurred at the research site. Determination of the number of samples using simple random sampling technique. This study uses the MICMAC analysis method which is used to categorize or classify a factor, based on the value of its influence and dependency. Based on the results of the research and discussion, it means that the existence of infrastructure, social capital, gender equality, traditional institutions, local culture, and employment are the key variables or key drivers in the involvement of women in supporting sustainable tourism in Penglipuran Village, Bangli Regency.